Finite element analysis of residual stresses during cold working. - Raj Arora, Prithvi; Tan, Jeffrey Meng Lee; Barnard, Christian; Asrar, Waqar
A two-dimensional finite element (FE) analysis, under plane stress condition has been carried using 2024-T3S1 aluminium alloy plate 6.35 mm thick with 6 mm diameter hole to study the cold expansion process. The material for the analysis is assumed to be isotropic, and a von Mises failure criterion along with linear isotropic hardening is used. The residual stress distribution has been obtained with pressure loading. The results indicate that large compressive tangential residual stresses were induced at the hole edge with reversed yielding on unloading. Reverse yielding was observed ifthe pressure loading P//oy > 1.2 attributed to the exceeding of raised compressive yield stress during unloading. A linear relationship has been observed between the cold work and the applied ND-pressure till a ND-pressure of 1.2 for the loading case and unloading case. A polynomial relationship is obtained giving the estimate of elastic-plastic boundary for a specified value of ND-pressure at the hole periphery.